Intermediated Investment Management - STOUGHTON, NEAL M.; WU, YOUCHANG; ZECHNER, JOSEF (Journal of Finance, 2011)
ABSTRACT Intermediaries such as financial advisers serve as an interface between portfolio managers and investors. A large fraction of their compensation is often provided through kickbacks from the portfolio manager. We provide an explanation for the widespread use of intermediaries and kickbacks. Depending on the degree of investor sophistication, kickbacks are used either for price discrimination or aggressive marketing. We explore the effects of these arrangements on fund size, flows, performance, and investor welfare. Kickbacks allow higher management fees to be charged, thereby lowering net returns. Competition among active portfolio managers reduces kickbacks and increases the independence of advisory services.